2012
DOI: 10.1152/japplphysiol.01308.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex and ovarian hormones on carotid baroreflex resetting and function during dynamic exercise in humans

Abstract: Kim A, Deo SH, Fisher JP, Fadel PJ. Effect of sex and ovarian hormones on carotid baroreflex resetting and function during dynamic exercise in humans. J Appl Physiol 112: 1361-1371, 2012. First published January 19, 2012 doi:10.1152/japplphysiol.01308.2011.-To date, no studies have examined whether there are either sex-or ovarian hormone-related alterations in arterial baroreflex resetting and function during dynamic exercise. Thus we studied 16 young men and 18 young women at rest and during leg cycling at 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 58 publications
2
22
0
Order By: Relevance
“…It is possible differences in techniques for measuring cardiac baroreflex sensitivity account for the disparity in findings. Studies using the neck pressure technique have shown no differences in sensitivity across the menstrual cycle (8,24), consistent with our results. We are the first to assess progesterone independently.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is possible differences in techniques for measuring cardiac baroreflex sensitivity account for the disparity in findings. Studies using the neck pressure technique have shown no differences in sensitivity across the menstrual cycle (8,24), consistent with our results. We are the first to assess progesterone independently.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have used a range of both neck pressure and neck suction to assess carotid baroreflex sensitivity and construct full baroreflex curves (24,35,37). We only assessed the responses to ϩ50 mmHg of neck pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cardiac ABR sensitivity has been reported to be increased during the late follicular phase compared with the early follicular and mid-luteal phases of the menstrual cycle (Tanaka et al, 2003). We recently used the variable pressure neck chamber technique to derive full carotid baroreflex stimulus-response curves in an attempt to better understand whether sex and/or fluctuations in endogenous ovarian hormones during the menstrual cycle modulate carotid baroreflex control of the heart (Kim et al, 2012). We noted a greater bradycardic response to carotid baroreceptor loading (i.e., simulated carotid hypertension) in young women at the early follicular phase of the menstrual cycle compared to young men.…”
Section: Sex Ovarian Hormones and Resting Abr Functionmentioning
confidence: 99%
“…Sex differences in baroreceptor reflex function have been reported in humans [28], [29], [27]. Young women have been shown to have lower resting sympathetic outflow and enhanced baroreflex function as compared to age matched men [30].…”
Section: Role Of the Brain In Sex Differences In Hypertension: Sympatmentioning
confidence: 99%